Higher stock plant nitrogen and phosphorus levels favor rooting on mini cuttings of tea tree. Issue 5 (23rd October 2021) - Lowe, Gail E.; Shepherd, Mervyn; Raymond, Carolyn; Rose, Terry
Abstract: The impact of N and P nutrition of stock plants of tea trees ( Melaleuca alternifolia ) on rooting and survival of cuttings was investigated in order to optimize adventitious rooting and growth of scion cuttings used for clonal propagation. High rates of 300 kg N ha –1 and 100 kg P ha –1 led to higher rooting, shoot elongation, and survival of the cuttings than low rates of 25 kg N ha –1 and 5 kg P ha –1, and are thus recommended for tea tree clonal propagation.